TiO2 Nanotubes and Their Photocatalytic Applications - Song, Yanyan; Lee, Kiyoung; Paramasivam, Indhumati; Kim, Doohun; Wilson, Benjamin P.; Schmuki, Patrik (wiley, 2023)
In the past 20 years, one-dimensional (1D) nanostructures have attracted enormous interest, primarily as such directional 1D nanostructures may provide unique electronic properties and a very high specific surface area. Except for carbon nanotubes, TiO2 is the most extensively studied material in nanotubular form (with more than 3000 publications over the past 10 years). The nanotubular architecture not only increases the specific surface area significantly, but also the directional electronic properties may change considerably. These effects may also combine to drastically improve the reaction/interaction between a device and the surrounding media, thereby making the system more (kinetically) effective. These features would drastically improve classic applications of TiO2, such as in photocatalysis or dye-sensitized solar cells (DSSCs), as well as expand the applications in new fields such as drug delivery, payload release, sensing platforms, filtration membranes, and so on.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Electrochemical anodization; Photocatalysis; Photocatalytic applications; TiO